2017
DOI: 10.1186/s13567-017-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Target organs for lymphocystis disease virus replication in gilthead seabream (Sparus aurata)

Abstract: The lymphocystis disease (LCD), the main viral pathology described in cultured gilthead seabream (Sparus aurata), is a self-limiting condition characterized by the appearance of hypertrophied fibroblasts (named lymphocysts) in the connective tissue of fish, primarily in the skin and fins. The causative agent of the disease is the Lymphocystis disease virus (LCDV), a member of the Iridoviridae family. In the present study, LCDV genome and transcripts were detected by real-time PCR in caudal fin, as well as in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
4
20
1
1
Order By: Relevance
“…Moreover, the high correlation (>90%) between LCDV DNA copies and the four SI categories confirmed this index is a good indicator of viral replication. It should be noted that although the liver is not the target organ for LCDV viral replication, this virus is able to replicate on it before spreading in integumentary system [3,14,24]. The selection of this organ appears also as a key point to precisely quantify DNA copies to prevent cross-contaminations between skin lesions in highly infected fish populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the high correlation (>90%) between LCDV DNA copies and the four SI categories confirmed this index is a good indicator of viral replication. It should be noted that although the liver is not the target organ for LCDV viral replication, this virus is able to replicate on it before spreading in integumentary system [3,14,24]. The selection of this organ appears also as a key point to precisely quantify DNA copies to prevent cross-contaminations between skin lesions in highly infected fish populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the skin is the organ with the highest number of viral DNA copies, LCDV also replicates in the liver [3,24]. This organ was selected as the target organ to quantify the viral DNA copies in each specimen, since it provides enough biomass for the nucleic acid isolation minimizing the risk of cross-contamination between individuals.…”
Section: Quantification Of Viral Dnamentioning
confidence: 99%
“…Classically, Iridoviridae are known to infect fish, amphibians, and insects. The four Iridoviridae carrying VILPs had all been originally isolated from fish, where they were known to cause systemic infections with a broad range of tissue tropism, including liver, pancreas, brain, kidney, and skin, and in the last cause tumor-like growths (29). As noted above, however, the sequences of VILPs are related to human insulin/IGF1 as closely or more closely than they are to fish or other species (Fig.…”
Section: Members Of the Iridoviridae Family Carry Genes Potentially Ementioning
confidence: 95%
“…However, skin or fin biopsies in histopathology test provided a definitive diagnosis of the type of lymphocystis tumor cells which can be easily differentiated by gross pathology. Valverde et al (2017) found that the lymphocystis cells was clusters of typical hypertrophied fibroblasts (lymphocysts). They also found dark inclusions within the cytoplasm and enclosed by a hyaline capsule, and were observed in the dermis of fin and skin where they were surrounded by an abundance of infammatory epithelioid that the inclusion body and hyaline capsules were predominant (Valverde et al 2017).…”
Section: Histological Observationsmentioning
confidence: 99%
“…Valverde et al (2017) found that the lymphocystis cells was clusters of typical hypertrophied fibroblasts (lymphocysts). They also found dark inclusions within the cytoplasm and enclosed by a hyaline capsule, and were observed in the dermis of fin and skin where they were surrounded by an abundance of infammatory epithelioid that the inclusion body and hyaline capsules were predominant (Valverde et al 2017). Pirarat et al (2011) explained that the LCDV was detectable not only in the skeletal muscle and gills lamellae but also in visceral organs such as spleen.…”
Section: Histological Observationsmentioning
confidence: 99%